"x equals -8" is the same as writing "x = -8" without quotes. This is basically saying x and -8 are the same thing at this point in time. Recall that x is simply a placeholder for a number.
Replace every copy of 'x' with -8 to go from this
8*x + 8*y = -48
to this
8*(-8) + 8*y = -48
-64 + 8*y = -48
---------------------------
Next add -64 to both sides
-64 + 8*y = -48
-64 + 8*y + 64 = -48 + 64
8*y = 16
Finally, divide both sides by 8 to isolate y
8*y = 16
8*y/8 = 16/8
y = 2
---------------------------
---------------------------
Answer: y = 2
As a check, we can plug both x = -8 and y = 2 into the original equation
8*x+8*y = -48
8*(-8)+8*2 = -48
-64+16 = -48
-48 = -48
the answer checks out